An immersed finite element material point (IFEMP) method for free surface fluid–structure interaction problems - Li, Ming-Jian; Lian, Yanping; Zhang, Xiong (Computer methods in applied mechanics and engineering, 2022)
The inherent nonlinearity of free surface fluid–structure interaction (FSI) problems challenges numerical methods in terms of efficiency and fidelity. In this article, we propose an immersed finite element material point method for the water entry fluid–structure interaction problems. In this method, the fluid domain is discretized by an improved incompressible material point method (iMPM) using both Eulerian and Lagrangian descriptions, while the solid domain is solved by finite element method (FEM). The interaction between the iMPM and FEM is handled by a sharp immersed interface approach. Moreover, weighted tracing points are designed to track the fluid–structure interface with a low time complexity; a particle rearranging method is developed to eliminate the numerical cavities, which are non-physical voids caused by the highly disordered particle distribution, from which the original iMPM for FSI problems suffers. Various free surface FSI problems are presented to demonstrate the accuracy and effectiveness of the proposed method. The computational results are compared with analytical, experimental, and simulation data from the literature, with good agreement in cases where such data is available. The proposed method is expected to be a powerful tool for free surface FSI problems.